The Use of angiotensin converting enzyme inhibitors in chronic kidney disease - a review of the literature - Jakub Sosnowski; Eliasz Panek; Damian Jasłowski; Mateusz Rzeszutko; Przemysław Raczkiewicz; Dominika Panasiuk; Mateusz Skrętowicz; Patrycja Szponarowicz; Bartosz Snopkowski; Tomasz Korzec (Kazimierz Wielki University, 2023)
Introduction: Chronic Kidney Disease (CKD) has become one of the most common chronic diseases of the XXI century and affects around 16% of the world's population. Despite the advancements of contemporary science and a range of therapeutic methods it considered a progressive and irreversible process. Nevertheless, use of ACEI halts the progression of the disease and postpones the necessity of renal replacement therapy and is the method of choice for this group of patients.  Purpose of the work: The article reviews current literature and writing regarding Chronic Kidney Disease (CKD) and the impact of ACEI on the progression of this condition.  Materials and methods: The sources available in the PubMed database have been analyzed using the keywords: "ACEI", "angiotensin-converting-enzyme inhibitors", "chronic kidney disease", "CKD". Related publications to the topic of the work have been selected and utilized.  Description of the state of knowledge: Pharmacological therapy using ACEI is the main method of treatment for patients with CKD and should primarily serve to reduce proteinuria and control blood pressure. It inhibits the progression of the disease and delays the development of end-stage renal failure. However, the treatment of CKD using ACEI is controversial in cases of advanced stages of the disease.  Summary: ACEI inhibitors are one of the major advances in the treatment of patients dealing with CKD. Due to the increasing number of cases of the disease being observed, further research will be needed regarding the use of these drugs. Particularly ambiguous is the therapy for patients with advanced, just before end-stage renal failure, which will require a more in-depth analysis of these cases.